All that glitters on chest radiology is not tuberculosis - Madhav Mahawar; Shreeshail Anjutagi; Keertivardhan D. Kulkarni; B. Likhitha (BLDE University Journal of Health Sciences)
This case report addresses the diagnostic challenges of tuberculosis (TB) in India, where many patients are misdiagnosed and may actually have other conditions, such as lung cancer. It details the case of a 64-year-old woman initially treated for TB, who was later diagnosed with adenocarcinoma after suffering side effects from antitubercular therapy. This case report highlights the critical need for accurate diagnosis through comprehensive evaluations and multidisciplinary discussions to prevent unnecessary treatments, improve patient outcomes, and enhance quality of life.